From Bright Windows to Dark Spots: Snow Cover Controls Melt Pond Optical Properties During Refreezing. Issue 23 (2nd December 2021) - Anhaus, P.; Katlein, C.; Nicolaus, M.; Hoppmann, M.; Haas, C.
Abstract: Melt ponds have a strong impact on the Arctic surface energy balance and the ice‐associated ecosystem because they transmit more solar radiation compared to bare ice. In the existing literature, melt ponds are considered as bright windows to the ocean, even during freeze‐up in autumn. In the central Arctic during the summer‐autumn transition in 2018, we encountered a situation where more snow accumulated on refrozen melt ponds compared to the adjacent bare ice, leading to a reduction in light transmittance of the ponds even below that of bare ice. Results from a radiative transfer model support this finding. This situation has not been described in the literature before, but has potentially strong implications for example on autumn ecosystem activity, oceanic heat budget, and thermodynamic ice growth. Plain Language Summary: Arctic sea ice is covered with snow during autumn, winter and spring. During summer, melt ponds evolve in response to surface melting. After snow fall starts again in autumn, these ponds can be filled with a lot of snow compared to bare ice because of their recessed surface. Indeed, during an expedition close to the North Pole in summer and autumn 2018, we measured a thick snow cover on ponds. This thick snow cover reduced the light availability underneath the ponds to levels below that underneath adjacent bare ice. This is a surprising finding, because it is different from the established theory of high light availability underneath melt ponds during both summer and autumn and how this is described in most computer models. It has consequences for our understanding of the ice‐associated ecosystem (organisms that live in and under sea ice). It might also impact the mass and energy balance of central Arctic sea ice during summer‐autumn transition when new sea ice starts forming. Key Points: Refrozen melt ponds may collect a thicker snow cover compared to bare sea ice due to their recessed topography Such snow‐covered melt ponds transmit less light compared to bare ice of similar type This scenario has not been documented before and should be accounted for in studies involving light in a refreezing Arctic Ocean